Soil Invertebrate Animals as Indicators of Contamination of Light Chestnut Ground of Southeast of Kazakhstan - Zulfia, Tukenova; Mereke, Alimzhanova; Saule, Kazybaeyeva; Kazhybek, Ashimuly; Oral, Zhylkybaev (International Journal of Engineering and Technology, 2018)
The use of living organisms as biological indicators for environmental change necessitates the development of a number of criteria on the basis of which it is possible to select indicator species. These include the biological activity of soils (mesofauna, enzymes). Bioindicators with a chronic anthropogenic load on the soil, in particular with prolonged application of fertilizers, can react to very weak effects due to dose accumulation, in addition, they make it unnecessary to use expensive and laborious physical and chemical methods for measuring biological parameters. The novelty of our research is based on the study of the influence of anthropogenic influences on the biological activity of soils in comparison with its basic indicators. This will allow us to establish a correlation between the soil fauna and the main traditional indicators of soil fertility, and significantly enhance their ecological significance in assessing agricultural practices in agricultural production. It has been revealed that the soils under study differ in relatively favorable physical properties, which in turn affects the distribution of the mesofauna. When the biological activity of soils was diagnosed, a decrease in the activity of soil mesofauna was noted in variants with high doses of phosphorus fertilizers depending on the type of soil. In light chestnut soils, meso-faunistic indices are reduced to (16 indÂ·m-2) and poor group diversity. The main representatives of the soil mesofauna are Carabidae, Formicidae, Lumbricidae, Scarabeidae. Typical species for fertilized soils are Carabidae, Lumbricidae, Scarabeidae. It was revealed that larvae of the mesofauna of soils from the family Curculionidae, Scarabaeidae are characteristic representatives. Representatives of these families can be used as bioindicators in conducting studies on the investigated soils. Bioindicator species of the investigated soils are present irrespective of the use of mineral fertilizers and, accordingly, the level of pesticide content.Â Â